(−)‐Englerin A is a Potent and Selective Activator of TRPC4 and TRPC5 Calcium Channels1. (23rd February 2015) - Akbulut, Yasemin; Gaunt, Hannah J.; Muraki, Katsuhiko; Ludlow, Melanie J.; Amer, Mohamed S.; Bruns, Alexander; Vasudev, Naveen S.; Radtke, Lea; Willot, Matthieu; Hahn, Sven; Seitz, Tobias; Ziegler, Slava; et al.
Abstract: Current therapies for common types of cancer such as renal cell cancer are often ineffective and unspecific, and novel pharmacological targets and approaches are in high demand. Here we show the unexpected possibility for the rapid and selective killing of renal cancer cells through activation of calcium‐permeable nonselective transient receptor potential canonical (TRPC) calcium channels by the sesquiterpene (−)‐englerin A. This compound was found to be a highly efficient, fast‐acting, potent, selective, and direct stimulator of TRPC4 and TRPC5 channels. TRPC4/5 activation through a high‐affinity extracellular (−)‐englerin A binding site may open up novel opportunities for drug discovery aimed at renal cancer.